1994
DOI: 10.1002/ijc.2910570412
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal‐growth‐factor‐receptor expression is associated with rapid tumor proliferation in bladder cancer

Abstract: Epidermal-growth-factor-receptor (EGF-r) expression has been proposed as a prognostic marker in bladder cancer and is associated with rapid proliferation in cell lines. Ninety-three fresh and 74 formalin-fixed bladder tumors were examined by fluorescence in situ hybridization (FISH) and immunohistochemistry to assess the relationship between EGF-r expression and proliferation as well as the prevalence of epidermal-growth-factor-receptor (EGF-r) gene amplification. EGF-r expression was strongly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
2
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 17 publications
8
68
2
6
Order By: Relevance
“…HER1 expression has been reported by a number of groups to be an informative prognostic indicator for TCC (17)(18)(19)(20). Increased HER1 expression has also been linked spatially to local increases in cell proliferation (21), suggesting a role for one or more HER1 ligands in aberrant urothelial cell growth. However, several reports have shown that EGF does not promote the growth of normal human urothelial cells (HUC) in serum-free medium, despite the presence of high-affinity EGF binding sites in these cells (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…HER1 expression has been reported by a number of groups to be an informative prognostic indicator for TCC (17)(18)(19)(20). Increased HER1 expression has also been linked spatially to local increases in cell proliferation (21), suggesting a role for one or more HER1 ligands in aberrant urothelial cell growth. However, several reports have shown that EGF does not promote the growth of normal human urothelial cells (HUC) in serum-free medium, despite the presence of high-affinity EGF binding sites in these cells (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of EG F R s are often found in bladder carcinoma and the over expression has proven closely related to tumour stage and malignancy grade (10)(11)(12)(13). U nfortunately, for targeted therapy, the EG F Rs are distributed among various normal tissues as well as tumours (14,15).…”
mentioning
confidence: 99%
“…3,4,8,[14][15][16] The expression of EGFR in glioblastoma, lung and bladder cancer is often associated with polysomy or amplification of EGFR. 4,17 Some studies suggested that the expression of EGFR and/or an increased EGFR copy number could be associated with responsiveness to erlotinib. 17 Our study confirmed data by Thomas et al 18 showing that EGFR overexpression in synovial sarcoma cannot be linked to an increase in EGFR gene copy number.…”
Section: Discussionmentioning
confidence: 99%
“…In some tumor types, EGFR expression is associated with poor clinical outcome. 3,4 In synovial sarcoma, the immunohistochemical detection of the EGFR protein has been first described in 1985. 5 Subsequent investigations demonstrated that EGFR expression is more frequently found in synovial sarcomas than in other soft tissue tumors.…”
mentioning
confidence: 99%